ÁBDIQÁDIR ShÍǴARMALARÍNDA TARIYXÍY TEMANÍŃ SÁWLELENIWI - Davletov, Barlıqbay Abdimuratovich (SCIENCE and SOCIETY, 2026)
The article analyzes the historical works of Abdikadir Bekimbet oglu, one of the Karakalpak folk poets. The poet’s historical works provide information about the livelihoods, lifestyles, and historical events of the people. The behavior of some officials is also criticized, and his historical poems are analyzed in context.